2010
DOI: 10.1016/j.jep.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a Severity of Dependence Scale for khat (SDS-khat)

Abstract: In this sample of Yemeni khat chewers the SDS-khat is recommended as a valid and reliable research tool for measuring psychological dependence upon khat. Further validation in other samples is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 60 publications
(77 reference statements)
10
70
2
Order By: Relevance
“…Predictive validity was demonstrated in relation to the need for treatment amongst drug users (30). The bilingual (Arabic and English) version of the Severity of khat dependence (SDS-khat) (21) was used in this study, and a total score of 6 was used as a cutoff to examine differences between those who are unlikely to be psychologically dependent on khat (total SDS-khat score = 5 or lower) and those who are likely to be khat dependent (total SDSkhat score = 6 or higher) (21). The Pittsburgh Sleep Quality Index (PSQI) consists of 19 questions that evaluate qualitative and quantitative dimensions of sleep disturbances (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive validity was demonstrated in relation to the need for treatment amongst drug users (30). The bilingual (Arabic and English) version of the Severity of khat dependence (SDS-khat) (21) was used in this study, and a total score of 6 was used as a cutoff to examine differences between those who are unlikely to be psychologically dependent on khat (total SDS-khat score = 5 or lower) and those who are likely to be khat dependent (total SDSkhat score = 6 or higher) (21). The Pittsburgh Sleep Quality Index (PSQI) consists of 19 questions that evaluate qualitative and quantitative dimensions of sleep disturbances (31).…”
Section: Methodsmentioning
confidence: 99%
“…Withdrawal symptoms after prolonged khat use are mild and may consist of lethargy, mild depression, slight trembling and recurrent nightmares (3,18). There is also evidence to indicate that khat users can develop a psychological dependence to khat (19,20) and a valid measure of khat dependence has been developed (21). Studies have found positive associations between khat dependence and khat-related biological measures (22), psychological and physical symptoms (23) and health problems (24).…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment and sample selection have been previously reported (Kassim & Croucher, 2010). This study involves a subsample (91regular cigarette smokers) of randomly recruited residents Yemeni khat chewers.…”
Section: Methodsmentioning
confidence: 99%
“…Levels (high and low) of cigarette dependence were measured using FTCD (Heatherton et al, 1991) as well as different levels of cigarette dependence (very low, low and medium) (Fagerstrom & Kozlowski, 1990). We also used SDS-Khat (Kassim & Croucher, 2010) to assess participants' severity of dependency on khat chewing. Adaptation/translation of the scale (FTCD) was carried out before the pilot study following the process of adaptation proposed by Hunt & Bhopal (2004).…”
Section: Methodsmentioning
confidence: 99%
“…The potential to induce psychological dependence is confirmed by a number of recent studies, using a version of the Severity of Dependence Scale (SDS) that has been adapted and validated for the study of khat dependence (25,26). It has been shown that khat chewers scoring high on this instrument show more khat-related behaviours and have higher khat alkaloid levels in their saliva (27).…”
Section: Adverse Effects Of Khat Use Dependencementioning
confidence: 96%